2019
DOI: 10.1002/rmv.2086
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Hepatitis E virus (HEV) field; lessons learned from human liver chimeric mice

Abstract: Summary Hepatitis E virus (HEV) is the most common cause of viral hepatitis globally, and it is an emerging pathogen in developed countries. In vivo studies of HEV have long been hindered due to the lack of an efficient small animal model. Recently, human liver chimeric mice were described as an elegant model to study chronic HEV infection. HEV infection was established in mice with humanized liver that were challenged with stool preparations containing HEV genotype (gt)1 and/or gt3. An increase in viral load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 119 publications
(313 reference statements)
0
30
0
Order By: Relevance
“…In this study, we assessed the replication of HEV in murine and human myeloid cells. Although mice are considered a query model for HEV [ 40 , 41 ], we tested the susceptibility of MMOs, MMACs, and murine BMDMs to HEV. We previously reported that non-transplanted immunocompromised mice (uPA +/+ /SCID and FRG) were not susceptible to HEV-1 and HEV-3 infection [ 32 , 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assessed the replication of HEV in murine and human myeloid cells. Although mice are considered a query model for HEV [ 40 , 41 ], we tested the susceptibility of MMOs, MMACs, and murine BMDMs to HEV. We previously reported that non-transplanted immunocompromised mice (uPA +/+ /SCID and FRG) were not susceptible to HEV-1 and HEV-3 infection [ 32 , 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not record a significant difference in the replication of HEV-1 and HEV-3 in HMOs, HMACs, and BMDMs. Although HEV-1 is more virulent than HEV-3 in infected patients and in vivo animal model [ 3 , 41 , 49 ], HEV-3 replicates more efficiently in the hepatoma-derived cell line, neuron-derived cell line, and placenta-derived cell line in vitro [ 18 , 29 , 31 ]. Some HEV-3 strains were adapted to grow in cell culture due to a recombination event resulting in an insertion of 174 ribonucleotides (58 amino acids) of the human ribosomal protein S17 gene into the viral genome [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEV-1 and HEV-2 are transmitted by the fecal–oral route, and they are mainly associated with waterborne HEV outbreaks in developing countries [ 4 , 5 ]. HEV-3 and HEV-4 infect humans and animals such as pigs, wild boars, deer, rabbits, cows, and goats [ 6 , 7 ]. They are zoonotic, infection is mainly transmitted to humans either by contact with these animals or the ingestion of undercooked meat, sausages, liver, or other products from them [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the replication of HEV-1 was inhibited in vitro in a swine kidney cell line, probably HEV-1 produced insufficient capsid protein for optimal assembly in swine cells [ 49 ]. Additionally, HEV was not replicating in the kidney of human liver chimeric mice, which was murine in its origin [ 36 , 50 ]…”
Section: Discussionmentioning
confidence: 99%